Expression of oxytocin in hypothalamus and reduction of nociceptive stress following administration of Kamikihi-to in female rats - Maruyama, Takashi; Shimizu, Makiko; Ikeda, Naofumi; Baba, Kazuhiko; Yoshimura, Mitsuhiro; Ueta, Yoichi (Frontiers in Pharmacology, 2022)
Hypothalamo-neurohypophysial oxytocin (OXT) plays an essential role in reproduction and in several socio-physiological functions, including stress reduction, anxiety relief, feeding suppression, social recognition, and trust building. Recent studies suggest that the central OXT system is also involved in antinociceptive and anti-inflammatory functions. Kamikihi-to (KKT), a Japanese traditional herbal (Kampo) medicine composed of 14 herbal ingredients, is clinically prescribed for patients with psychological symptoms, including anxiety, depression, and insomnia, and it has been associated with OXT expression. We investigated the antinociceptive response and OXT expression according to sex and the effects of KKT pre administration in a rat model. We found that nociceptive responses measured via the hot plate and formalin tests were attenuated following the administration of KKT-enriched feed for 4 weeks. The observation of mRFP1 fluorescence in OXT-mRFP1 transgenic rats revealed that KKT-administered rats showed increased expression of OXT in the magnocellular and parvocellular paraventricular nucleus of the hypothalamus. Food intake in the KKT-pre-administered group significantly decreased after cholecystokinin (CCK)-8 administration. Our results suggest that KKT is involved in the attenuation of nociceptive stress in female rats by enhancing the expression of OXT in the hypothalamus.